Never Alone in the Crowd: A Microscopic Crowd Model Based on Emotional Contagion - Lhommet, Margaux; Lourdeaux, D.; Barthès, Jean-Paul (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
This paper presents a system designed to create crisis-simulation that shows the emergence of crowd behavior from individual behaviors, based on the emotional contagion phenomenon. Many studies from psychology and sociology mention this phenomenon but very little was found about what parameters determine it. This paper proposes a model of emotional contagion based on individual personality and relationships. A key contribution of this work is describing a computational mapping from OCEAN personality traits to the strength of, and susceptibility to, emotional contagion. This model is implemented into a multi-agent system where everyone is represented by an emotional, social and cognitive agent.